Effects of Inspiratory Muscle Training on Respiratory Muscle Strength, Lactate Accumulation and Exercise Tolerance in Amateur Runners: A Randomized Controlled Trial - Zhe Ren; Junxia Guo; Yurong He; Yu Luo; Hao Wu (Life)
Objective: This study investigated the dose–response relationship of inspiratory muscle training (IMT) on respiratory muscle strength, lactic acid accumulation and exercise tolerance in amateur runners. Methods: Thirty male amateur runners were randomly assigned to three groups: a high-intensity IMT (HIMT) group, a low-intensity IMT (LIMT) group, and a control group. In addition to their regular training regimen, the high-intensity and low-intensity IMT groups underwent a supervised IMT protocol for a duration of 8 weeks. The primary outcome measures included maximal inspiratory pressure (MIP), maximal expiratory pressure (MEP), time to exhaustion (TTE), blood lactate (BLa), rate of perceived exertion (RPE), and rate of perceived breathlessness (RPB). Secondary outcomes encompassed VO2 max, forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and the FEV1/FVC ratio. Results: After 8 weeks of IMT, the MIP of HIMT and LIMT were significantly improved (p < 0.01), and the MEP of both groups also increased (p < 0.01). There were no significant changes in FVC and FEV1 (p > 0.05), but only FEV1/FVC in HIMT was significantly improved (p < 0.01). Exercise testing showed a significant increase in TTE in both the HIMT and low LIMT groups (p < 0.01). Post-exercise RPE scores were lower in both the HIMT group (p < 0.01) and LIMT group (p < 0.05), and both HIMT and LIMT groups’ post-exercise RPB scores were also reduced in both (p < 0.05). In addition, blood lactate accumulation was significantly lower in both HIMT (p < 0.01) and LIMT (p < 0.05). There were no significant changes in VO2 max (p > 0.05) and HR peak (p > 0.05). Conclusion: IMT for 8 weeks can improve respiratory muscle strength, prolong exercise time, improve blood lactate accumulation, subjective fatigue, and dyspnea during exercise. Among them, high-intensity IMT can better improve exercise tolerance.